CLINICAL CASES FROM THE PRACTICE OF MEMBERS OF THE SURGICAL INFECTIOUS SOCIETY OF NORTH AMERICA (SIS-NA) - Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
This description provides publicly available information regarding interesting clinical cases that have been borrowed from the descriptions of members of the SIS. We intend to present these cases with descriptions, as we believe that they will be very useful and interesting for subscribers of our scientific and practical journal. So, we present a description of the following three interesting clinical cases: Extensive Bilateral Gluteal Necrotizing Myositis after International Cosmetic Tourism (Robel Beyene MD, Jeffrey Shupp MD, Anthony Shiflett MD, Chadi Abouassaly MD); An improvised adaptation of negative pressure wound therapy in Nicaragua for the management of intraabdominal sepsis (Roberto J. Silva Doña MD, Hector Nunez, Andrew H. Stephen); Sweet Syndrome Manifesting as a Case of Necrotizing Soft Fasciitis (John S. Young MD, Daithi S. Heffernan MD).